Influence of low-Z impurity on the stabilization of m/n= 2/1 tearing/locked modes in EAST. (1st May 2022) - Xu, Ming; Liang, Yunfeng; Wei, Lai; Duan, Yanmin; Shi, Tonghui; Zhao, Hailin; Xu, Liqing; Zhou, Ruijie; Zhang, Ling; Gu, Shuai; Gao, Wei; Zhang, Yang; et al.
Abstract: The impact of the low- Z impurity concentration on mode stabilization has been investigated in the EAST tokamak. A series of tearing modes (TMs) with multiple helicities are excited by the low- Z (carbon) impurity concentration, and the dominant mode structure features m / n = 2/1 magnetic islands that propagate in the electron diamagnetic drift direction ( m and n are poloidal and toroidal mode numbers, respectively). The m / n = 2/1 locked modes (LMs) can be formed by the redistribution of low- Z impurity concentration, and are unlocked spontaneously due to the decrease in the impurity concentration, where the width of the magnetic islands can reach w ≈ 5 cm ( w / a ≈ 0.1, a is the minor radius). The increase in the electromagnetic brake torque is the primary reason for the mode locking, and the ' O '-point of the m / n = 2/1 magnetic islands is locked by the tungsten protector limiter (toroidal position: −0.4 π ⩽ ϕ ⩽ −0.3 π ) with separation of Δ ϕ ≈ 0. The 3D asymmetric structure of the m / n = 2/1 magnetic islands is formed for the interaction with the tungsten protector limiter, and the electromagnetic interaction decreases dramatically for the separation of Δ ϕ ⩾ 0.2 π . The mode excitation and locking mechanisms can be illustrated by the 'hysteresis effect' between the low- Z impurity concentration and the width of the m / n = 2/1 magnetic islands; namely, the growth of magnetic islands is modulated by the low- Z impurity concentration, and the rotation velocity is decelerated accordingly. However, the intrinsic mechanism for the unlocking of m / n = 2/1 LMs is complicated by considering the concentration of the low- Z impurity, and the possible unlocking mechanism is discussed. Therefore, understanding the relationship between the impurities and magnetic islands is more important for optimization of the control techniques (resonant magnetic perturbations → LMs, electron cyclotron resonant heating (ECRH) → neoclassical tearing mode (NTM), impurity seeding → major collapse, etc).